Blood-Sucking Fly Icosta ardeae – Its Distribution and Probable Role in Circulation of West-Nile FeverVirus - A. V. Matyukhin; A. N. Matrosov; A. M. Porshakov; A. A. Kuznetsov (Проблемы особо опасных инфекций, 2013)
Communication comprises materials on distribution of blood-sucking fly, Icosta ardeae, in the territory of the Russian Federation and bordering states. Based on the analysis of literature data, collection assets, and personal investigations assumed has been the fact that this species is more widely spread in the local fauna than it was anticipated earlier. The fly parasitizes on the birds of 11 species, orders - ciconiiformes (storks), shore (wading) birds, Gruiformes, and fowl-like birds (Galliformes). More often I. ardeae is seen among bitterns – 43 % of the findings, abundance index –5,9. Therewith, put forward is the suggestion concerning the role of the species and other Hippoboscidae in the process of persistence and distribution of West-Nile fever virus. Studies of this group of insects can be of use for identification of mechanisms that benefit natural foci extension and development as regards various infectious diseases.